Quality of life of high risk pregnant women during prenatal care - Ivyna Pires Gadelha; Priscila de Souza Aquino; Marianne Maia Dutra Balsells; Flaviane Fabrício Diniz; Ana Karina Bezerra Pinheiro; Samila Gomes Ribeiro; Régia Christina Moura Barbosa Castro
ABSTRACT Objective: to analyze the quality of life of high-risk pregnant women. Methods: an observational and cross-sectional study, carried out in a tertiary maternity hospital located in Fortaleza, with 276 high-risk pregnant women. A questionnaire was applied containing socioddemographic, clinical and obstetric data and The Mother-Generated Index. Descriptive analyzes were performed using the Jamovi statistical program®, version 0.9. Results: most areas were negatively influenced by pregnancy. "Satisfaction with pregnancy", "family relationship" and "relationship with the partner" obtained the highest means of primary score, while "physical condition/disposition" and "financing" obtained the lowest means. The highest secondary scores were in "satisfaction with pregnancy", "family relationship" and "relationship with the partner", while the lowest were in "financing" and "psychological/emotional". Conclusion: the total primary score mean was 6.03, suggesting a good quality of life. The Mother Generated Index made it possible to identify aspects of life that go beyond pre-formulated assessments of the construct.